If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -5x + 7 + 2x = -8 Reorder the terms: 7 + -5x + 2x = -8 Combine like terms: -5x + 2x = -3x 7 + -3x = -8 Solving 7 + -3x = -8 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-7' to each side of the equation. 7 + -7 + -3x = -8 + -7 Combine like terms: 7 + -7 = 0 0 + -3x = -8 + -7 -3x = -8 + -7 Combine like terms: -8 + -7 = -15 -3x = -15 Divide each side by '-3'. x = 5 Simplifying x = 5
| 1=5x+3x-7 | | 1=p+12 | | 3*-2=5*4-26 | | -21n=483 | | 3sinx+4cosx^2=0 | | r+2=15 | | -3*-2=x+2 | | 2u+10=26 | | (2x-5)(3x+4)= | | 5x(63-16)= | | m^3-6=0 | | (4w-8)(w+3)=0 | | -2in(x)+in(y)=in(6) | | 6x^2-11x-13=5(x^2-1)+3 | | 8+6x=7x-5 | | V+4=-5 | | Y=-16x+20x+5 | | 3X^(7/3)-6=0 | | 5x^3=85 | | (4y-8)(3y+7)=0 | | w=mxf+eforx | | z(z+7)=0 | | 12x6/6x3 | | -4q-(-7.3)=45.9 | | 1x+.12x=34000 | | (X6)6/x3 | | 12x-8=14x-34 | | -3.6+2z=13.6 | | -3x+5y=34whenx+3y-18 | | 8(p+1)-8= | | 31.9=-7+4m | | -3x+5y=34 |